Disassociating Lung Mechanics and Oxygenation in Pediatric Acute Respiratory Distress Syndrome*. Issue 7 (July 2017) - Yehya, Nadir; Thomas, Neal J.
Abstract : Objectives: Both oxygenation and peak inspiratory pressure are associated with mortality in pediatric acute respiratory distress syndrome. Since oxygenation and respiratory mechanics are linked, it is difficult to identify which variables, pressure or oxygenation, are independently associated with outcome. We aimed to determine whether respiratory mechanics (peak inspiratory pressure, positive end-expiratory pressure, ΔP [PIP minus PEEP], tidal volume, dynamic compliance [Cdyn ]) or oxygenation (PaO2/FIO2) was associated with mortality. Design: Prospective, observational, cohort study. Setting: University affiliated PICU. Patients: Mechanically ventilated children with acute respiratory distress syndrome (Berlin). Interventions: None. Measurements and Main Results: Peak inspiratory pressure, positive end-expiratory pressure, ΔP, tidal volume, Cdyn, and PaO2/FIO2 were collected at acute respiratory distress syndrome onset and at 24 hours in 352 children between 2011 and 2016. At acute respiratory distress syndrome onset, neither mechanical variables nor PaO2/FIO2 were associated with mortality. At 24 hours, peak inspiratory pressure, positive end-expiratory pressure, ΔP were higher, and Cdyn and PaO2/FIO2 lower, in nonsurvivors. In multivariable logistic regression, PaO2/FIO2 at 24 hours and ΔPaO2/FIO2 (change in PaO2/FIO2 over the first 24 hr) were associated with mortality, whereas pressure variables were not. Both oxygenation and pressure variables were associated with duration of ventilation in multivariable competing risk regression. Conclusions: Improvements in oxygenation, but not in respiratory mechanics, were associated with lower mortality in pediatric acute respiratory distress syndrome. Future trials of mechanical ventilation in children should focus on oxygenation (higher PaO2/FIO2) rather than lower peak inspiratory pressure or ΔP, as oxygenation was more consistently associated with outcome. Abstract : Supplemental Digital Content is available in the text.